Kualitas mikrob dan sel somatik dalam susu yang berasal dari peternakan sapi perah di lokasi dataran tinggi dan dataran rendah - Jannah, Zahratul; Isdoni, Isdoni; Komala, Iyep; Pisestyani, Herwin; Herwin (Current Biomedicine, 2023)
Background: Consumers have the right to consume safe and healthy fresh milk. One of the factors that affect the productivity and quality of milk is the altitude of the location and environmental conditions around the farm. Objective: This research aimed to determine the differences in microbial quality and the somatic cell count (SCC) in milk between farms in the highlands (Cijeruk Farm, Bogor) and lowlands (Pondok Ranggon Farm, East Jakarta). Methods: This study observed the total plate count (TPC), the number of Staphylococcus aureus, and SCC. Microbial testing was carried out using the plate count method and the somatic cells count used the Breed method. The data were analyzed statistically using Mann-Whitney U and Chi-square. Results: The results showed that TPC, S. aureus, and SCC of milk from Pondok Ranggon located in the lowlands were higher than those of milk from Cijeruk located in the highlands. The average of TPC, S. aureus, and SCC in milk from Cijeruk were 1.6×104 ± 1.5×104 CFU/mL, 1.3×103 ± 4.2×103 CFU/mL, and 1,795,000 ± 1,838,791 cells/mL, respectively. The average of TPC, S. aureus, and SCC in milk from the Pondok Ranggon were 3.5×105 ± 1.0×106 CFU/mL, 1.7×105 ± 6.3×104 CFU/mL and 3,032,222 ± 4,348,654 cells/mL, respectively. This research showed that the location of the rearing area has relationship with S. aureus in milk (P<0.05). Conclusion: It was concluded that microbial status and the somatic cell count are influenced by differences in livestock areas.